(3GdegGQGJ GdCSGSjI aj GdJQHjI GdHOfjI dQjGV GdCWaGd GdCShjGA h Phj GdGMJjGLGJ GdNGUIs - (3GdScQj NjQjI EHQGgjes; (3aGWeI ahRj YHO GdQMeGf s ((3GdGScfOQjIs (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQs, 2005)
(3HQGeL GdJQHjI GdHOfjI GdYGeI ddCWaGd GdCShjGA aj CgOGagG GdQFjSjI,eY JbOje HQGeL GdJQHjI GdHOfjI GdNGUI ddCWaGd Phj GdGMJjGLGJ GdNGUI aj cGaI GdYfGUQ GdCSGSjI ddfeh , JgOa cd efge Gdi JWhjQ cd GddjGbI GdHOfjI(B.s
Keywords: (3GdJQHjI GdHOfjI(B_(3GdCWaGds